Tissue Transglutaminase-Regulated Transformed Growth Factor-β1 in the Parasite Links Schistosoma japonicum Infection with Liver Fibrosis. (23rd June 2015) - Tang, Juanjuan; Zhu, Xunmin; Zhao, Jingjing; Fung, Mingchiu; Li, Yinyan; Gao, Zhiyan; Yan, Suikai; Li, Xiaomin; Ji, Xiaofang; Su, Fang; Li, Zi
Abstract : Transforming growth factor (TGF- β 1) is among the strongest factors of liver fibrogenesis, but its association with Schistosoma -caused liver fibrosis is controversial. Tissue transglutaminase (tTG) is the principal enzyme controlling TGF- β 1 maturation and contributes to Sj -infected liver fibrosis. Here we aim to explore the consistency between tTG and TGF- β 1 and TGF- β 1 source and its correlation with liver fibrosis after Sj -infection. TGF- β 1 was upregulated at weeks 6 and 8 upon liver fibrosis induction. During tTG inhibition, TGF- β 1 level decreased in sera and liver of infected mice. TGF- β 1 showed positive staining in liver containing Sj adult worms and eggs. TGF- β 1 was also detected in Sj adult worm sections, soluble egg antigen and Sj adult worm antigen, and adult worms' culture medium. The TGF- β 1 mature peptide cDNA sequence and its extended sequence were amplified through RT-PCR and RACE-PCR using adult worms as template, and sequence is analyzed and loaded to NCBI GenBank (number GQ338152.1). TGF- β 1 transcript in Sj eggs was higher than in adult worms. In Sj -infected liver, transcriptional level of TGF- β 1 from Sj, but not mouse liver, correlated with liver fibrosis extent. This study provides evidence that tTG regulates TGF- β 1 and illustrates the importance of targeting tTG in treating Sj infection-induced fibrosis.